Looking at resilience among transgender and gender diverse people in Portugal: Gender affirmation paths and parenting aspirations - Moleiro, C.; Alarcão, V.; Giami, A. (Social Sciences, 2023)
The transgender and gender diverse (TGGD) population is highly diverse. To date, research on the association of the various family–parenthood aspirations of TGGD people with distinct affirming paths and identities remains scarce. A survey was conducted aiming to characterize the TGGD population’s diversity and socio-demographic profile. A community-based convenience sample of 115 self-identified TGGD adults living in Portugal was collected. Most of the participants (69%) did not have any children, 10% had children of their own, and about 20% did not have children in the present but reported their intensions to have children in the future. The results were discussed, highlighting the heterogeneity found in terms of sociodemographic characteristics, gender identification, and gender affirmation pathways (social, legal, and medical), with a focus on the participants’ parenthood aspirations. The under- or non-representation of transgender individuals in population surveys, such as demographic and health surveys, is a barrier to understanding the social determinants and health disparities faced by this population.